Miniature bonsai : the complete guide to super-mini bonsai - Iwai, Terutoshi (Tuttle Publishing, 2017)
Miniature Bonsai reveals the Japanese art of super-mini bonsai gardening. This new book by Japanese expert Terutoshi Iwai shows you how to create exquisite super-mini bonsai that last for year with the right care! From choosing the plants and containers to buying and mixing the growing medium, to maintaining and displaying your bonsai--Iwai provides all the information needed to successfully cultivate miniature bonsai. He includes instructions for growing many different varieties of miniature bonsai including pines, maples, junipers, oaks and a variety of flowering trees.